Method for testing thermal performance of glass fiber surface impregnating compound
Testing the wetting agent-containing and bare glass fiber section samples of glass fiber through DSC, directly obtaining its thermal performance parameters, solving the problem that traditional methods are difficult to test, and achieving rapid, environmentally friendly and accurate thermal performance analysis of wetting agents.
Patent Information
- Application Number
- CN202411293237.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-24
AI Technical Summary
When traditional methods test the thermal properties of glass fiber surface wetting agents, it is difficult to obtain clear results, and the extraction rate of the indirect method is not high, time-consuming, and not environmentally friendly.
A differential scanning calorimeter (DSC) was used to combine electronic balances and solid crucibles to seal the cut segment samples containing wetting agents and bare glass fibers to obtain the DSC map to analyze thermal performance parameters, avoiding the use of chemical reagents.
The thermal performance parameters of the glass fiber surface wetting agent are achieved quickly and obviously obtained, which is simple, fast and environmentally friendly, representing the situation of all the glass fiber surface wetting agent and avoiding the limitations of traditional methods.
Smart Images

Figure CN119178785A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of glass fibers, and in particular to a method for testing the thermal properties of a surface sizing agent for glass fibers. Background Art
[0002] The sizing agent is a layer of high molecular polymer that must be coated in the production of glass fiber. It plays a vital role in the production of glass fiber and its later performance. However, its mass accounts for a very small proportion, only about 0.1-2% of the total mass of the glass fiber. In the production process, the sizing agent can ensure the smoothness of glass fiber drawing, and play a role in lubricating, protecting, bonding and bundling the glass raw fibers. In terms of later performance, the sizing agent can give the glass fiber certain properties, such as stiffness and dispersibility, to ensure the characteristics required for subsequent processing. On the other hand, it can greatly improve the interfacial compatibility between glass fiber and resin, and maximize the physical and mechanical properties of the material. Therefore, the sizing agent on the surface of glass fiber is the core of determining the performance of a glass fiber, and directly affects the application of glass fiber. In the process of developing glass fiber, it is inevitable to test the thermal performance parameters of the sizing agent on the surface of glass fiber, such as the common glass transition temperature or melting temperature.
[0003] The traditional thermal performance test method uses a differential scanning calorimeter (DSC) for testing, that is, a certain amount of glass fiber sample is weighed and sealed in a crucible, and then the test is performed directly. The reference plate of this method is an empty plate. In this case, the heat flow signal generated by the relatively high content of the inorganic part cannot be deducted, so the baseline will fluctuate. In addition, the wetting agent content on the surface of the glass fiber is too low. If the baseline flatness of the DSC equipment itself is not small enough, the DSC spectrum collected at the end will either change very slightly and not obviously, or change slightly and complicatedly, making it difficult to distinguish the part representing the wetting agent.
[0004] If an indirect method is used for testing, that is, to test the thermal properties of the wetting agent on the surface of the glass fiber, the wetting agent needs to be separated from the glass fiber first. For example, Chinese patents CN102564991A and CN114088654A both disclose a method of separating the wetting agent on the surface by Soxhlet extraction and then characterizing it. The defect of the extraction method is that the wetting agent on the surface of the glass fiber cannot reach 100% due to the compatibility relationship with the selected solvent. Therefore, the characterization analysis of the extracted sample is not the information of all the wetting agents on the surface of the glass fiber, which has great limitations; in addition, the extraction process is cumbersome and time-consuming, and it will produce waste reagents, which is not environmentally friendly. Summary of the invention
[0005] Based on the above existing technical problems, the present application provides a method for testing the thermal properties of the wetting agent on the surface of glass fiber, which can directly test the glass fiber and quickly and clearly obtain the thermal performance parameters of the wetting agent on the surface of the glass fiber. The test is direct, simple, fast and environmentally friendly.
[0006] Specifically, according to a first aspect of the present application, a method for testing the thermal properties of a glass fiber surface sizing is provided, comprising the following steps:
[0007] S1: Select a differential scanning calorimeter (DSC), an electronic balance, and a solid crucible;
[0008] S2: prepare the glass fiber containing sizing agent and bare glass fiber to be tested, and cut them into sections respectively;
[0009] S3: preparing a sample of the glass fiber: weighing the empty crucible, the glass fiber containing the sizing agent, and the bare glass fiber respectively, and then filling the cut glass fiber containing the sizing agent and the bare glass fiber into a solid crucible respectively, and then sealing the crucible to obtain a sample disk and a bare glass fiber disk to be tested;
[0010] S4: Place the sample disk on the sample stage of the DSC device, and the bare glass fiber disk on the reference stage of the DSC device. Then input the mass, heating rate, and start and end temperatures. Test under an inert atmosphere to obtain a DSC spectrum. The thermal performance parameters of the wetting agent on the glass fiber surface can be obtained by analyzing and annotating the DSC spectrum.
[0011] In the present application, steps S1 and S2 can be replaced in sequence according to actual conditions and are not limited by the order of numbers.
[0012] The thermal performance parameters include glass transition temperature, melting temperature, crystallization temperature, melting enthalpy, and crystallization enthalpy.
[0013] The straightness of the baseline of the differential scanning calorimeter (DSC) in step S1 should be ≤10uw. The accuracy of the electronic balance should be d≤0.01mg.
[0014] The solid crucible in step S1 includes two types: standard and Tzero, and the crucible cover includes two types: sealed and non-sealed.
[0015] Furthermore, the material of the crucible and the cover includes aluminum, copper, graphite, platinum, etc., preferably aluminum.
[0016] Furthermore, the crucible has a diameter of 5-6 mm and a wall thickness of 1.7-2.6 mm.
[0017] The glass fiber containing the sizing agent in step S2 includes direct yarn, plied yarn, chopped yarn and their respective products, including glass fiber cloth, felt, etc., and its combustible content is ≥0.4%.
[0018] The bare glass fiber in step S2 is obtained by high-temperature calcination to remove the sizing agent. Specifically, the calcination temperature is 600-650° C. and the calcination time is 1-2 hours.
[0019] The length of the glass fiber segments in step S2 is controlled to be 2-6 mm, preferably 3-5 mm.
[0020] The sample disc made of glass fiber containing sizing agent in step S3 is placed on the sample stage of the DSC instrument; the reference disc made of bare glass fiber is placed on the reference stage of the instrument.
[0021] The filling in step S3 is performed by stacking in warp and weft to load more glass fibers into the crucible.
[0022] The weight of the glass fiber containing the sizing agent or the bare glass fiber in step S3 is ≥30 mg, preferably 40-50 mg.
[0023] The input masses in step S4 are respectively the masses of the glass fiber containing the sizing agent, the bare glass fiber, and the respective crucibles and (empty crucible and cover).
[0024] The heating rate in step S4 is 3-20°C / min, preferably 8-15°C / min, and more preferably 10°C / min.
[0025] The starting and ending temperatures in step S4 are -90-300°C, preferably -90-200°C.
[0026] The inert atmosphere in step S4 includes high-purity nitrogen or high-purity argon, with a purity of >99% and a flow rate of 50±5 ml / min.
[0027] Compared with the prior art, the technical solution of this application has the following advantages:
[0028] (1) The test conducted according to this method can obtain very obvious thermal performance parameters, breaking the limitation of traditional test methods that it is difficult to obtain clear results.
[0029] (2) The thermal performance parameters obtained by this method can represent the entire sizing agent condition on the glass fiber surface, avoiding the disadvantage of using indirect testing methods that can only reflect the thermal performance parameters of part of the sizing agent.
[0030] (3) This method directly tests the glass fiber without the use of chemical reagents, and has low cost. It avoids the pollution and harm caused by the use of chemical reagents and has the advantages of high environmental protection and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] According to the following description of the drawings, the purpose, features and advantages of the specific implementation cases of the present application are described in detail, which will help those skilled in the art to better understand the practical significance of the present application.
[0032] Figure 1 This is the DSC scanning spectrum of SMC yarn A.
[0033] Figure 2 This is the DSC scanning spectrum of sheet yarn B.
[0034] Figure 3 This is the DSC scanning spectrum of direct yarn C for wind power.
[0035] Figure 4 This is the DSC scanning spectrum of direct yarn D for pultrusion.
[0036] Figure 5 This is the DSC scanning spectrum of chopped yarn E.
[0037] Figure 6 This is the DSC scanning spectrum of chopped yarn F.
[0038] Figure 7 This is the DSC scanning spectrum of direct yarn G for LFT.
[0039] Figure 8 This is the DSC scanning spectrum of H of thermoplastic chopped yarn.
[0040] Fig. 9 This is the test diagram of sample A using the traditional method.
[0041] Fig.10 This is the test diagram of sample C using the traditional method.
[0042] Fig.11 This is the test diagram of sample H using the traditional method.
[0043] Fig.12 This is the test diagram of sample F using the traditional method. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the specific embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. It should be noted that the embodiments in the present application and the features in the embodiments can be combined with each other in the absence of conflict. The present application will be described in detail below in conjunction with the embodiments.
[0045] Exploring the subject matter described in this application by referring to specific implementation cases will help those skilled in the art to have a deeper understanding of the significance of this application. These implementation cases are not limited to the scope of protection, examples or applicability described in the claims. Without exceeding the scope of this specification, the addition ratio and arrangement of the elements under discussion can be adjusted. Each example can add various processes, or replace, omit, or supplement each component according to actual needs. In addition, the features described specifically can be combined in different examples.
[0046] Example 1
[0047] 1. Select DSC equipment (TA Company, USA), electronic balance and solid crucible.
[0048] 2. Prepare four types of glass fibers (glass fibers containing sizing agents), namely, plied untwisted roving A for SMC, plied untwisted roving B for sheet materials, direct yarn C for wind power, and direct yarn D for profiles. Take some of the four types of glass fibers AD, and put A and B into a Ma Fuel furnace and burn them at 625℃ for 1h to obtain their corresponding bare glass fibers; put C and D into a Ma Fuel furnace and burn them at 640℃ for 1h to obtain their corresponding bare glass fibers; cut the four types of glass fibers AD and the corresponding bare glass fibers into several sections of 4mm respectively.
[0049] 3. Weigh and record the weight of the empty crucible and lid, AD sample yarn and bare glass fiber respectively. Finally, seal the solid aluminum crucible for testing. The specific weights are shown in the table below:
[0050]
[0051] The cut sample yarn and the bare glass fiber are stacked in sequence and placed in a solid aluminum crucible, which is then covered and sealed to obtain a sample disk and a bare glass fiber disk to be tested.
[0052] 4. Place the sample disc prepared from bare glass fiber on the reference platform of the DSC, and the sample disc prepared from sample yarn on the sample platform. After turning on the DSC equipment as required, enter the weights in step 3 in the software and set the test program: high-purity nitrogen, flow rate of 50ml / min, first cool to -50℃, keep constant temperature for 2min, and then heat to 100℃ at 10℃ / min; start the test after setting.
[0053] Mark the thermal performance parameter Tg on the heating curve. Figure 1-Figure 4 As can be seen from the graph, this test method can clearly test the Tg values of the four glass fiber surface sizing agents. It can also be seen that different types of rovings have different formulas and present different Tg values. It can also distinguish the distribution of multiple Tg values in the same formula, which can provide strong data support for the development and improvement of glass fiber sizing agent formulas.
[0054] Example 2
[0055] 1. Select DSC equipment, electronic balance and solid crucible.
[0056] 2. Prepare two kinds of chopped glass fibers (glass fibers containing sizing agents), namely thermoplastic chopped yarns E and F. Take part of the two types of glass fibers EF, put them into a furnace and burn them at 625℃ for 1 hour to obtain the corresponding bare glass fibers; because the chopped length of the chopped yarn is 3 or 4.5mm, it does not need to be cut into segments.
[0057] 3. Stack the two types of glass fibers, EF, in sequence and place them in a solid aluminum crucible. Weigh and record the weights of the empty crucible and cover, EF sample yarn and bare glass fiber. Finally, seal the solid aluminum crucible for testing. The specific weights are shown in the table below:
[0058]
[0059] The cut sample yarn and the bare glass fiber are stacked in sequence and placed in a solid aluminum crucible, which is then covered and sealed to obtain a sample disk and a bare glass fiber disk to be tested.
[0060] 4. Place the sample disc prepared from bare glass fiber on the reference platform of the DSC, and the sample disc prepared from sample yarn on the sample platform. After turning on the DSC equipment as required, enter the weights in step 3 in the software, and set the test program: cool down to -90℃, keep the temperature constant for 2 minutes, and heat up to 100℃ at 10℃ / min; start the test after setting.
[0061] Mark the thermal performance parameter Tg on the heating curve, see Figure 5-Figure 6 As can be seen from the graph, this test method can clearly test the Tg values of the two glass fiber surface impregnation agents. Different types of chopped yarns have different formulas. The acetone extraction rate of this type of yarn is extremely low, which will greatly limit the characterization test of the Tg of the surface impregnation agent. The method of this application can directly test and break through this limitation, providing convenience for the development of formulas.
[0062] Example 3
[0063] 1. Select DSC equipment, electronic balance and solid crucible.
[0064] 2. Prepare two kinds of glass fibers (glass fibers containing impregnation agents), namely direct yarn G for LFT and chopped yarn H. Take part of the two kinds of glass fibers G and H, put them into a boiling furnace and burn them at 610°C for 1.5 hours to obtain their respective bare glass fibers; cut the two kinds of glass fibers G and H and the corresponding bare glass fibers into several sections of 5 mm respectively.
[0065] 3. Weigh and record the weight of the empty crucible and lid, G and H sample yarns and bare glass fiber respectively. Finally, seal the solid aluminum crucible for testing. The specific weights are shown in the table below:
[0066]
[0067] The cut sample yarn and the bare glass fiber are stacked in sequence and placed in a solid aluminum crucible, which is then covered and sealed to obtain a sample disk and a bare glass fiber disk to be tested.
[0068] 4. Place the sample disc prepared from bare glass fiber on the reference platform of the DSC, and the sample disc prepared from sample yarn on the sample platform. After turning on the DSC equipment as required, enter the weights in step 3 in the software and set the test program: 20℃ / min heating to 200℃; 10℃ / min cooling to -50℃; constant temperature for 5min; 10℃ / min heating to 200℃, and start the test after setting.
[0069] Take the cooling curve and the second heating curve, and mark the thermal performance parameters melting temperature and crystallization temperature. Figure 7-8 . It can be seen from the graph that this test method can clearly test the melting temperature and crystallization temperature values of the two glass fiber surface impregnation agents G and H. For different types of reinforced polyolefin yarns, the melting temperature and crystallization temperature of the impregnation agent on their surface are different; if this type of impregnation agent is removed by extraction, it needs to be extracted with toluene at high temperature before testing; and the extract cannot be completely extracted, and the crystallization ability of the extracted material is affected by the solvent and is not in the original state, so it is difficult to characterize. The method of the present application directly conducts test characterization, which can greatly provide strong reference data for research and development.
[0070] Comparative test example
[0071] Samples A, C, H and F in the above implementation cases were tested by DSC according to the traditional thermal performance test method, that is, a certain amount of glass fiber samples were weighed and sealed in a crucible, and then directly tested. The comparison of the test graphs is as follows: the graph tested by the method of the present application has a more stable overall curve trend, the transition peak of Tg or melting temperature is relatively obvious, and more transition peaks can be tested, which can reflect that the test results of the method of the present application are more detailed and accurate.
[0072] In summary, the method for testing the thermal properties of the glass fiber surface sizing of the present application can directly test the glass fiber, and can quickly and clearly obtain the thermal performance parameters of the glass fiber surface sizing, and the test is direct, simple, fast and environmentally friendly. The above is only a preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents; and these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for testing the thermal properties of a glass fiber surface sizing, characterized in that: The following steps are involved: S1: Select a differential scanning calorimeter, an electronic balance, and a solid crucible; S2: prepare the glass fiber containing sizing agent and bare glass fiber to be tested, and cut them into sections respectively; S3: preparing a sample of the glass fiber: weighing the empty crucible, the glass fiber containing the sizing agent, and the bare glass fiber respectively, and then filling the cut glass fiber containing the sizing agent and the bare glass fiber into a solid crucible respectively, and then sealing the crucible to obtain a sample disk and a bare glass fiber disk to be tested; S4: Place the sample disk into the sample stage of a differential scanning calorimeter, place the bare glass fiber disk into the reference stage of the differential scanning calorimeter, then input the mass, heating rate, and start and end temperatures, and perform the test under an inert atmosphere.
2. The method for testing the thermal properties of glass fiber surface sizing according to claim 1, characterized in that: The bare glass fiber is obtained by high-temperature calcination to remove the impregnating agent; the calcination temperature is 600-650° C. and the calcination time is 1-2 hours.
3. The method for testing the thermal properties of glass fiber surface sizing according to claim 1, characterized in that: The heating rate is 3-20°C / min.
4. The method for testing the thermal properties of glass fiber surface sizing according to claim 1, characterized in that: The starting and ending temperatures are -90-300°C.
5. The method for testing the thermal properties of glass fiber surface sizing according to claim 1, characterized in that: The input masses are respectively the masses of the glass fiber containing the sizing agent, the bare glass fiber, and the respective crucibles and covers.
6. The method for testing the thermal properties of glass fiber surface sizing according to claim 1, characterized in that: The weight of the glass fiber containing the sizing agent or the bare glass fiber is controlled to be ≥30 mg; and the length of the cut section is controlled to be 2-6 mm.
7. The method for testing the thermal properties of glass fiber surface sizing according to claim 1, characterized in that: The glass fiber containing the sizing agent includes direct yarn, plied yarn, chopped yarn and their respective products, and the combustible content is ≥ 0.4%; The thermal properties include glass transition temperature, melting temperature, crystallization temperature, melting enthalpy and crystallization enthalpy.
8. The method for testing the thermal properties of glass fiber surface sizing according to claim 1, characterized in that: The filling is carried out in a warp and weft stacking manner.
9. The method for testing the thermal properties of glass fiber surface sizing according to claim 1, characterized in that: The inert atmosphere includes high-purity nitrogen or high-purity argon, with a purity of more than 99% and a flow rate of 50±5 ml / min.
10. The method for testing the thermal properties of glass fiber surface sizing according to claim 1, characterized in that: The straightness of the baseline of the differential scanning calorimeter is ≤10uw, and the accuracy of the electronic balance is d≤0.01mg.
Citation Information
Patent Citations
Quantitative analysis method of glass fiber surface impregnating compound
CN102564991A
Method for evaluating effectiveness of glass fiber coating and application thereof
CN114088654A
